العنف اللفظي و دوره في صناعة خطاب الكراهية دراسة ميدانية بابتدائية الشهيد فرحات بن شهرة الأغواط - بن السايخ خديجة نور; شتوح سعاد; بن لحبيب بشير (My University, 2022)
This study dealt with the subject of verbal violence and its role in the manufacture of hate speech in the educational environment. Our aim in this study was to give a clear picture about verbal violence and the extent of its role in the manufacture of hate speech, as well as to confirm the relationship between them. Where we followed the descriptive approach in completing our research, and we also used the questionnaire in this study This study was applied to a sample of male and female students. the hub: This research focused on two partial hypotheses and a general hypothesis. To prove the validity of the general hypothesis: The conclusion of this study, according to the previous results, is that verbal violence has a major role in the manufacture of hate speech in the educational environment.